A high performance solder paste for BC batteries

By using high-performance solder paste on BC batteries, combining bismuth, nanosilver and other components and flux, the problem of solder forming a shadowed area on BC batteries is solved, the light transmittance and conductivity are improved, and the solder reliability is enhanced It can reduce the internal resistance of the solder joint and is suitable for high-temperature welding.

CN118905497BActive Publication Date: 2024-12-24SUZHOU TONYSHARE ELECTRONICS MATERIALS TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411388894.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-24
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The existing solder forms a shaded area on the BC battery, affecting the battery performance, and the traditional solder has poor heat resistance, which increases the possibility of damage to the soldering equipment and electronic components.

Method used

Using high-performance solder paste, by adding bismuth, nanosilver, vanadium, dysprosium, nanotin and other components to the tin-based alloy powder, and adding compound active agents, boric acid, resin film forming agents, and sodium fluoride to the flux The components are combined with tin dioxide and titanium dioxide nanoparticles to enhance light transmittance and electrical conductivity.

Benefits of technology

It improves the light transmittance and electrical conductivity of solder paste, reduces thermal stress, enhances solder reliability, improves signal transmission performance, and maintains stability at high temperatures, reduces the internal resistance of solder joints, and improves the durability of solder joints.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of welding, and in particular to a high-performance solder paste for BC batteries. The tin-based alloy powder and the soldering flux are composed of a mass ratio of (83-87):(13-17); the tin-based alloy powder comprises 10-30% of bismuth, 0.6-1.8% of nano silver particles, 0.02-0.1% of vanadium, 0.02-0.1% of dysprosium, 0.2-0.9% of indium, and the balance is nano tin; the soldering flux comprises the following components in mass percentage: 5-14% of a composite active agent, 3-6% of boric acid, 2-5% of a defoaming agent, 10-20% of a resin film-forming agent, 5-10% of a wetting agent, 0.02-0.1% of sodium fluoride, 3-6% of polyacetylene powder, 1-3% of titanium dioxide nano particles, 2-3% of tin dioxide, 2-10% of a thixotropic agent, and the balance is a solvent. The solder paste provided by the present invention helps to reduce thermal stress, improve electrical conductivity, heat aging resistance and light penetration, can be used in applications requiring electrical connection, which is crucial to ensure the stability and reliability of signal transmission, and improves electron mobility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding, and in particular to a high-performance solder paste for BC batteries. Background Art

[0002] Sn-Pb solder has been used in the electronics industry for quite a long time. Due to its low melting point, high cost performance and easy availability, it has become the most important low-temperature solder system. The lowest melting point of tin-lead solder is 183°C. It belongs to medium-low temperature solder and is widely used in the fields of welding of non-ferrous metals, food containers, buildings, machinery and pipelines. However, with the advent of the information age, electronic products emerge in an endless stream. While these electronic products benefit mankind, the lead they contain is increasingly polluting the ecological environment and human health.

[0003] At present, the lead-free solders that are more recognized by the industry are mainly Sn-Ag-Cu and Sn-Bi, especially the former. Because Sn-Ag-Cu alloy solders are easy to obtain, have fewer technical problems, good compatibility with traditional solders, and high reliability of solder joints. However, it is unrealistic to completely replace tin-lead solders with Sn-Ag-Cu alloy solders. Apart from cost factors, the most important thing is that the melting point of Sn-Ag-Cu solders is higher than that of tin-lead solders, which leads to an increase in welding temperature. It is easy to cause thermal damage to components with poor heat resistance, causing the flat substrate to bend and deform, increasing the possibility of damage. This means that the use of Sn-Ag-Cu lead-free solders poses severe challenges to a series of projects such as welding equipment, welding processes, and the temperature resistance of electronic components and substrate materials.

[0004] The eutectic melting point of Sn-Bi solder is very low, only 139°C, which is lower than the traditional Sn-37Pb solder alloy (183°C). The low melting point makes it very advantageous in the outer layer of graded packaging and close to the temperature-sensitive inner layer. It also shows excellent properties in the 100°C temperature cycle test after surface assembly, and its application in precision electronic equipment also shows that it has good signal transmission performance. Due to the poor thermal fatigue resistance and ductility of SnBi eutectic solder, its welding reliability is insufficient and the wire processing is difficult, which limits its further promotion and application.

[0005] BC cell, full name Back Contact solar cell, is an advanced solar cell technology. The characteristic of this cell is that all electrode contacts are placed on the back of the cell, thus eliminating the shading of the front grid line, increasing the area of ​​the cell absorbing sunlight, and thus improving the photoelectric conversion efficiency. The production and manufacturing of BC cells is difficult, with high requirements for substrate materials, complex processes, and high-precision equipment and technical support. The production yield is relatively low, which increases the difficulty and cost of production. Photon penetration refers to the ability of light waves to pass through a certain medium without being absorbed or reflected. In metals, photon penetration is usually poor because metals have free electrons, which interact with the electromagnetic field of the incident light, causing the energy of the light wave to be absorbed and converted into kinetic energy of the electrons, which is usually manifested as the reflectivity of the metal. Therefore, traditional solder or solder paste will form a shadow area on the BC cell, affecting the performance of the cell. Summary of the invention

[0006] Based on this, the present invention proposes a high-performance solder paste for BC batteries, which has high light transmittance and electrical conductivity, as well as signal transmission performance.

[0007] According to one aspect of the present invention, a high-performance solder paste for BC batteries is provided, wherein the tin-based alloy powder and the soldering flux are composed of a mass ratio of (83-87):(13-17);

[0008] The tin-based alloy powder comprises 10-30% bismuth, 0.6-1.8% nano silver particles, 0.02-0.1% vanadium, 0.02-0.1% dysprosium, 0.2-0.9% indium, and the balance is nano tin;

[0009] The soldering flux comprises the following components in percentage by mass: 5-14% of a compound active agent, 3-6% of boric acid, 2-5% of a defoaming agent, 10-20% of a resin film-forming agent, 5-10% of a wetting agent, 0.02-0.1% of sodium fluoride, 3-6% of polyacetylene powder, 1-3% of titanium dioxide nanoparticles, 2-3% of tin dioxide, 2-10% of a thixotropic agent, and the balance is a solvent.

[0010] According to an embodiment of the present invention, solder paste is applied to BC cells in the photovoltaic industry through screen printing and scraper printing, that is, there are requirements for the diameter of the metal powder.

[0011] According to an embodiment of the present invention, the particle size of the bismuth is 40-80 nm.

[0012] According to an embodiment of the present invention, the particle size of the vanadium is 50-100 μm.

[0013] According to an embodiment of the present invention, the particle size of the dysprosium is 100-150 nm.

[0014] According to an embodiment of the present invention, the particle size of the indium is 30-100 nm.

[0015] According to an embodiment of the present invention, the particle size of the nano-silver particles is 10-50 nm.

[0016] According to an embodiment of the present invention, the composition of lactic acid-glycolic acid copolymer and an active ingredient comprises one or more of malonic acid, glutaric acid, adipic acid, citric acid, and suberic acid.

[0017] According to an embodiment of the present invention, the resin film-forming agent is at least one of hydrogenated rosin resin, polymerized rosin, disproportionated rosin resin, acid-modified rosin, acrylic resin, and phenolic resin.

[0018] According to an embodiment of the present invention, the defoaming agent is one or more of mineral oil, silicone and polyether compounds.

[0019] According to an embodiment of the present invention, the wetting agent is composed of isononyl isononanoate and low molecular weight hydrogenated polyisobutylene in a mass ratio of (7-10): (2-5).

[0020] According to an embodiment of the present invention, the particle size of the nano-tin is 20-100 nm.

[0021] According to an embodiment of the present invention, the thixotropic agent is polyamide, hydrogenated castor oil or amide-modified hydrogenated castor oil or a mixture thereof.

[0022] According to an embodiment of the present invention, the polyether compound is one or more of polyoxyethylene glyceryl ether, polyoxypropyl glyceryl ether and polyoxypropyl polyoxyethyl glyceryl ether.

[0023] According to an embodiment of the present invention, the organic silicon is methyl silicone oil and / or dimethyl silicone oil.

[0024] It can be seen from the above technical solution that the high-performance solder paste for BC batteries provided by the present invention has the following beneficial effects:

[0025] The present invention provides a high-performance solder paste for BC batteries. It can be adjusted to match the thermal expansion coefficients of different materials, which helps to reduce thermal stress and improve the reliability of electronic components. Due to its good electrical conductivity, it can be used in applications that require electrical connections, such as interconnection points of circuit boards. The solder paste provided by the present invention effectively improves its heat aging resistance and light penetration, which is crucial to ensuring the stability and reliability of signal transmission, and improves electron mobility, which has a positive effect on improving signal transmission efficiency and interconnection performance. And it exhibits good corrosion resistance in certain environments, which helps to maintain the integrity of the signal transmission path.

[0026] The present invention can improve the light penetration by doping tin dioxide and titanium dioxide in the solder paste. Nanosilver and nanotin can enhance the light penetration due to their local surface plasmon resonance (LSPR) effect. Titanium dioxide nanoparticles have certain penetration in the ultraviolet and near-infrared regions. Polyacetylene, as a conjugated polymer, has excellent light capture ability and light penetration due to its π conjugated system. Polyacetylene itself is a semiconductor, but its conductivity can be significantly improved by doping, and it helps to enhance the adhesion between the solder paste and the material to be welded, improve the stability of the solder paste, and can withstand high temperatures during the welding process without decomposition. DETAILED DESCRIPTION

[0027] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0028] According to one aspect of the present invention, a high-performance solder paste for BC batteries is provided, wherein the tin-based alloy powder and the soldering flux are composed of a mass ratio of (83-87):(13-17);

[0029] The tin-based alloy powder comprises 10-30% bismuth, 0.6-1.8% nano silver particles, 0.02-0.1% vanadium, 0.02-0.1% dysprosium, 0.2-0.9% indium, and the balance is nano tin;

[0030] The soldering flux includes the following components in percentage by mass: 5-14% of a compound active agent, 3-6% of boric acid, 2-5% of a defoaming agent, 10-20% of a resin film-forming agent, 5-10% of a wetting agent, 0.02-0.1% of sodium fluoride, 3-6% of polyacetylene powder, 1-3% of titanium dioxide nanoparticles, 2-3% of tin dioxide, 2-10% of a thixotropic agent, and the balance is a solvent.

[0031] Tin is a very commonly used solder metal, especially as the main component in tin-lead alloys. Tin has good soldering properties and a low melting point. Silver solder is widely used due to its excellent electrical and thermal conductivity. Silver is also often used to increase the strength and corrosion resistance of the solder.

[0032] Bismuth (Bi), tin (Sn), dysprosium (Dy), indium (In), silver (Ag) and vanadium (V) elements can form eutectic low-melting-point alloys. Dysprosium metal can be used as a magneto-optical storage material with high recording speed and reading sensitivity, improving the magnetic and thermal properties of the alloy. The addition of dysprosium will indirectly affect the melting point by forming a solid solution or affecting the microstructure of the alloy.

[0033] Fluorides are added to alloys as fluxes to form low-melting alloys. These fluorides can form low-melting eutectic mixtures with alloys, thereby lowering the melting point of the alloy, facilitating melting or welding at lower temperatures, improving the corrosion resistance and wear resistance of solder paste, and helping to improve current efficiency. Sodium fluoride can form low-melting alloys with bismuth. The formation principle of these eutectic mixtures is based on the interaction between different components, resulting in a mixture with a melting point lower than the melting point of each component alone. Sodium fluoride plays a role in lowering the melting point and improving performance in these mixtures.

[0034] Tin dioxide and titanium dioxide can be doped into solder paste to improve light penetration. Nanosilver and nanotin can enhance light penetration due to their local surface plasmon resonance (LSPR) effect. Titanium dioxide nanoparticles have certain penetration in the ultraviolet and near-infrared regions. Polyacetylene, as a conjugated polymer, has excellent light capture and light penetration due to its π conjugated system. Polyacetylene itself is a semiconductor, but its conductivity can be significantly improved by doping. It also helps to enhance the adhesion between solder paste and the material being welded, improve the stability of solder paste, and can withstand high temperatures during welding without decomposition.

[0035] According to the embodiment of the present invention, the particle size of the nano silver particles is 10-50 nm. The nano silver particles with such fine structure can more effectively improve the conductivity of the battery.

[0036] Nanosilver and nanotin may exhibit physical and chemical properties different from those of macroscopic materials due to their unique size effects, including thermal properties. If nanosilver is used as a dispersed phase in an alloy, it will affect the melting point of the alloy by affecting its grain size, grain boundary characteristics or phase distribution.

[0037] According to an embodiment of the present invention, the particle size of the nano-tin is 20-100 nm.

[0038] Nano-tin may exhibit different optical properties from bulk tin. Compared with traditional tin, nano-tin has better electrical conductivity and a lower melting point, which allows it to melt at a lower temperature during the welding process, helping to reduce the heat-affected zone and avoid damage to sensitive electronic components. Nano-tin solder exhibits good wettability during the welding process and better mechanical properties, such as higher strength and hardness, which helps to improve the quality and reliability of solder joints, which helps to improve the durability of solder joints, which has potential applications in electronic devices and sensors, especially in high-performance electronic packaging and microelectronics.

[0039] According to an embodiment of the present invention, the composition of lactic acid-glycolic acid copolymer and active ingredients, wherein the active ingredients include one or more of malonic acid, glutaric acid, adipic acid, citric acid, and suberic acid, can not only improve the conductivity of the battery, but also effectively reduce the internal resistance of the solder joint.

[0040] According to an embodiment of the present invention, the resin film former is at least one of hydrogenated rosin resin, polymerized rosin, disproportionated rosin resin, acid-modified rosin, acrylic resin, and phenolic resin, and these resin film formers can effectively improve the electrochemical performance of the battery.

[0041] According to an embodiment of the present invention, the defoaming agent is one or more of mineral oil, silicone and polyether compounds, and these defoaming agents can effectively improve the leveling and stability of the solder paste.

[0042] According to an embodiment of the present invention, the wetting agent is composed of isononyl isononanoate and low molecular weight hydrogenated polyisobutylene in a mass ratio of (7-10): (2-5). These wetting agents can effectively improve the coating and reversibility of the solder paste.

[0043] According to an embodiment of the present invention, the thixotropic agent is polyamide, hydrogenated castor oil or amide-modified hydrogenated castor oil or a mixture thereof.

[0044] According to an embodiment of the present invention, the polyether compound is one or more of polyoxyethylene glycerol ether, polyoxypropyl glycerol ether and polyoxypropyl polyoxyethyl glycerol ether. These polyether compounds can both improve the conductivity of the solder paste and reduce the internal resistance of the solder paste.

[0045] According to an embodiment of the present invention, the organic silicone is methyl silicone oil and / or dimethyl silicone oil.

[0046] Example 1

[0047] Provided is a high-performance solder paste for BC batteries, wherein the tin-based alloy powder and the flux are composed of a mass ratio of 83:17;

[0048] The tin-based alloy powder includes 10% bismuth, 1.8% nano silver particles, 0.1% vanadium, 0.1% dysprosium, 0.9% indium, and 87.1% nano tin;

[0049] The soldering flux includes the following components in percentage by mass: 5% of compound active agent, 3% of boric acid, 2% of polyoxyethylene glycerol ether, 20% of hydrogenated rosin resin, 5% of wetting agent, 0.02% of sodium fluoride, 3% of polyacetylene powder, 1% of titanium dioxide nanoparticles, 2% of tin dioxide, 2% of polyamide, and the balance is solvent.

[0050] The compound active agent is a mixture of lactic acid-glycolic acid copolymer, citric acid and suberic acid in a ratio of 2:1:1.

[0051] The particle size of the nano-silver particles is 50 nm, and the particle size of the nano-tin is 20 nm.

[0052] The wetting agent is composed of isononyl isononanoate and low molecular weight hydrogenated polyisobutylene in a mass ratio of 8:3.

[0053] Example 2

[0054] Provided is a high-performance solder paste for BC batteries, wherein the tin-based alloy powder and the flux are composed of a mass ratio of 87:13;

[0055] The tin-based alloy powder includes 20% bismuth, 1% nano silver particles, 0.05% vanadium, 0.05% dysprosium, 0.6% indium, and 78.3% nano tin;

[0056] The soldering flux includes the following components in percentage by mass: 14% of compound active agent, 6% of boric acid, 5% of methyl silicone oil, 10% of disproportionated rosin resin, 10% of wetting agent, 0.1% of sodium fluoride, 6% of polyacetylene powder, 3% of titanium dioxide nanoparticles, 3% of tin dioxide, 10% of hydrogenated castor oil, and the balance is solvent.

[0057] The compound active agent is a mixture of lactic acid-glycolic acid copolymer, glutaric acid and adipic acid in a ratio of 2:1:1.

[0058] The particle size of the nano-silver particles is 30nm, and the particle size of the nano-tin is 60nm.

[0059] The wetting agent is composed of isononyl isononanoate and low molecular weight hydrogenated polyisobutylene in a mass ratio of 7:5.

[0060] Example 3

[0061] Provided is a high-performance solder paste for BC batteries, wherein the tin-based alloy powder and the flux are composed of a mass ratio of 85:15;

[0062] The tin-based alloy powder includes 30% bismuth, 0.6% nano silver particles, 0.02% vanadium, 0.02% dysprosium, 0.2% indium, and 69.16% nano tin;

[0063] The soldering flux includes the following components in percentage by mass: 10% of a compound active agent, 4% of boric acid, 5% of mineral oil, 15% of acid-modified rosin, 8% of a wetting agent, 0.05% of sodium fluoride, 4% of polyacetylene powder, 2% of titanium dioxide nanoparticles, 2.5% of tin dioxide, 6% of amide-modified hydrogenated castor oil, and the balance is a solvent.

[0064] The compound active agent is a mixture of lactic acid-glycolic acid copolymer and malonic acid in a ratio of 1:1.

[0065] The particle size of the nano-silver particles is 10 nm, and the particle size of the nano-tin is 100 nm.

[0066] The wetting agent is composed of isononyl isononanoate and low molecular weight hydrogenated polyisobutylene in a mass ratio of 10:2.

[0067] Experimental Example 1:

[0068] The solder pastes prepared in Examples 1-3 were tested for relevant indicators, specifically as follows:

[0069] Viscosity test: According to the test method of JIS-Z-3284 / IPC-TM-6502.4.34, at 25±1℃, use NDJ-7 rotary viscometer to rotate continuously at 7.5 rpm for 2 minutes, and read the value after stabilization.

[0070] Thermal collapse: According to the IPC-TM-6502.4.35 test method, a thermal collapse test was carried out using a 0.1 mm thick template (placed on a 150 ± 10 ° C metal hot plate for 10 minutes).

[0071] Copper plate corrosion test: Test according to Appendix 4 of JIS.Z.3197.

[0072] Detection of residual flux rate: weigh solder paste with a mass of m1, in which the proportion of flux in the solder paste is ρ, and apply the solder paste on a 1010 aluminum substrate with a mass of m2, a thickness of 1mm, a length and a width of 40mm. Then place the test solder piece on an induction cooker with a constant temperature of 120°C and preheat it for 15S. Then place it on a lead-free tin furnace with a constant temperature of 250°C. The solder spreads and forms a solder joint. After keeping it for 60s, remove the test solder piece and then directly weigh the test solder piece to obtain its mass m3. The residual rate f after welding is calculated according to the following formula: f=[m3-m2-(1-ρ)m1)] / (ρm1).

[0073] Light transmittance: A test piece was prepared by attaching a plate glass with a thickness of 3 mm to the functional film side of a light-transmitting laminate (hereinafter referred to as a film) with a thickness of 25 μm. The test piece was used to measure the transmission spectrum of wavelengths of 380 nm to 780 nm using a spectrophotometer to determine the visible light transmittance. The appearance was confirmed by visually reflecting the light of a three-wavelength fluorescent lamp onto the film from a distance of 30 cm. The case where the visible light transmittance was 60% or more was considered to have good light transmittance, and the case where the visible light transmittance was less than 60% was considered to have poor light transmittance.

[0074] Packaging effect: The solder paste provided in Examples 1-3 was used to perform soldering multiple times, and its average thermal conductivity and defective rate were measured.

[0075] Table 1. Performance tests of Examples 1-3

[0076] Example 1 Example 2 Example 3 ViscosityPa.s 122 131 128 Thermal collapse qualified qualified qualified Copper plate corrosion No corrosion No corrosion No corrosion Flux volatilization % 8.46 7.74 8.15 Thermal conductivity % 67 68 67 Defective rate % 0.2 0.3 0.2 Light transmittance good good good

[0077] The present invention provides a high-performance solder paste for BC batteries. It can be adjusted to match the thermal expansion coefficients of different materials, which helps to reduce thermal stress and improve the reliability of electronic components. Due to its good electrical conductivity, it can be used in applications that require electrical connections, such as interconnection points of circuit boards. The solder paste provided by the present invention effectively improves its heat aging resistance and light penetration, which is crucial to ensuring the stability and reliability of signal transmission, and improves electron mobility, which has a positive effect on improving signal transmission efficiency and interconnection performance. And it exhibits good corrosion resistance in certain environments, which helps to maintain the integrity of the signal transmission path.

[0078] The present invention can improve the light penetration by doping tin dioxide and titanium dioxide in the solder paste. Nanosilver and nanotin can enhance the light penetration due to their local surface plasmon resonance (LSPR) effect. Titanium dioxide nanoparticles have certain penetration in the ultraviolet and near-infrared regions. Polyacetylene, as a conjugated polymer, has excellent light capture ability and light penetration due to its π conjugated system. Polyacetylene itself is a semiconductor, but its conductivity can be significantly improved by doping, and it helps to enhance the adhesion between the solder paste and the material to be welded, improve the stability of the solder paste, and can withstand high temperatures during the welding process without decomposition.

[0079] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-performance solder paste for BC batteries, characterized in that: The tin-based alloy powder and the flux are composed of a mass ratio of (83-87):(13-17); The tin-based alloy powder comprises 10-30% bismuth, 0.6-1.8% nano silver particles, 0.02-0.1% vanadium, 0.02-0.1% dysprosium, 0.2-0.9% indium, and the balance is nano tin; The soldering flux comprises the following components in percentage by mass: 5-14% of a compound active agent, 3-6% of boric acid, 2-5% of a defoaming agent, 10-20% of a resin film-forming agent, 5-10% of a wetting agent, 0.02-0.1% of sodium fluoride, 3-6% of polyacetylene powder, 1-3% of titanium dioxide nanoparticles, 2-3% of tin dioxide, 2-10% of a thixotropic agent, and the balance is a solvent; The compound active agent is a composition of a lactic acid-glycolic acid copolymer and an active ingredient, and the active ingredient includes one or more of malonic acid, glutaric acid, adipic acid, citric acid, and suberic acid.

2. The high-performance solder paste for BC batteries according to claim 1, characterized in that: The particle size of the nano silver particles is 10 to 50 nm.

3. The high-performance solder paste for BC batteries according to claim 1, characterized in that: The resin film-forming agent is at least one of hydrogenated rosin resin, polymerized rosin, disproportionated rosin resin, acid-modified rosin, acrylic resin, and phenolic resin.

4. The high-performance solder paste for BC batteries according to claim 1, characterized in that: The defoaming agent is one or more of mineral oil, silicone and polyether compounds.

5. The high-performance solder paste for BC batteries according to claim 1, characterized in that: The wetting agent is composed of isononyl isononanoate and low molecular weight hydrogenated polyisobutylene in a mass ratio of (7-10): (2-5).

6. The high-performance solder paste for BC batteries according to claim 1, characterized in that: The particle size of the nano tin is 20-100 nm.

7. The high-performance solder paste for BC batteries according to claim 1, characterized in that: The thixotropic agent is polyamide, hydrogenated castor oil or a mixture thereof.

8. The high-performance solder paste for BC batteries according to claim 4, characterized in that: The polyether compound is one or more of polyoxyethylene glyceryl ether, polyoxypropyl glyceryl ether and polyoxypropyl polyoxyethyl glyceryl ether.

9. The high-performance solder paste for BC batteries according to claim 4, characterized in that: The organic silicon is methyl silicone oil and / or dimethyl silicone oil.